If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 6) = 3(x + 7) Reorder the terms: 2(6 + x) = 3(x + 7) (6 * 2 + x * 2) = 3(x + 7) (12 + 2x) = 3(x + 7) Reorder the terms: 12 + 2x = 3(7 + x) 12 + 2x = (7 * 3 + x * 3) 12 + 2x = (21 + 3x) Solving 12 + 2x = 21 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + 2x + -3x = 21 + 3x + -3x Combine like terms: 2x + -3x = -1x 12 + -1x = 21 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + -1x = 21 + 0 12 + -1x = 21 Add '-12' to each side of the equation. 12 + -12 + -1x = 21 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 21 + -12 -1x = 21 + -12 Combine like terms: 21 + -12 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9
| x+1=12x-1 | | 3/5*(-1/6) | | 3r/10=6 | | -2.73+x=-.3 | | q/-5=18 | | 2log(3x+5)=4 | | -19.5=9.5x-5.5x | | 12(x+1)=-3 | | 22=x-7.8 | | 14-5x=-52 | | 121=4x+7 | | 4(x-5)=2(x+2) | | x+15+75=x | | (x-lnx*2x)/x^4 | | -3x+8x=10 | | 2n-3/7=1n-2/5 | | x+15=x+75 | | -6x+8=-3x-10 | | 6x-3x=-15 | | x^2-2x=20.085 | | 3n-6n=-12 | | xsquared+6x+2=3 | | 5x+5-6x=1 | | -24=4(x+6) | | R-3-8=-12 | | y^2-16y-100=0 | | R-4-7r=-10 | | -3u-(-7)=-4 | | 4u+10=-5(u+7) | | 3x+x=2x-10 | | 3(9-3x)=27 | | 2(3a+9b)= |